An Application of Photovoltaic Appropriate Technology as Garden Lighting at Tourist Area of Gangga Murmas Tree House North Lombok District - Umam, Khotibul; El Amin, Faris (CV. Creative Tugu Pena, 2023)
Park lighting in the Gangga Murmas Tree House Tourism Area, which is more precisely Gangga Hamlet, Genggelang Village, Gangga District, North Lombok Regency, is not sufficient. Without park lighting, tourist locations will resemble a dead zone at night and experience a decline in visitors. Therefore, the Community Service Team of the Madura State Islamic Institute through the 3T area community empowerment service provides a solution to illuminating the Gangga Murmas Tree House Tourism Area by utilizing new renewable energy Photovoltaic monocrystalline type to provide lighting at night. The installation of landscape lighting using polycrystalline technology is determined by the outcomes of location surveys and observations. The implementation carried out in the Gangga Murmas Tree House Tourism Area was carried out in several stages, namely: observation, preparation of garden light design, training and maintenance, performance testing, and tool evaluation. After the project was finished in two months, a solar power plant with a 2800Wh capacity that can power 40 lamps with a combined 120Watt capacity was created. The placement of garden lights to improve the tourism sector also received a positive response from the community and the manager of the Gangga Murmas Tree House Tourism Area. Keywords: Photovoltaic Appropriate Technology, Garden Lighting